DAMPAK PEMBERIAN LEVAMISOL HIDROKLORIDA TERHADAP TITER ANTIBODI PASCA VAKSINASI VIRUS AVIAN INFLUENZA PADA AYAM PETELUR - Lili Zalizar (Faculty of Animal Science, Universitas Brawijaya, 2010)
Levamisole has been reported can enhance immune response of animals against disease (immunomodulator).Giving levamisole before vaccination Avian Influenza (AI) virus is expected to increase antibody level (humoral immune response) against the disease. These experiments use an experimental method with a completely randomized design.A total of 105 laying chickens were divided into three groups: group one were AI vaccinated without given levamisole hydrochloride; group two were given levamisole hydrochloride 3 days respectively before AI vaccination and group three were given levamisole hydrochloride 7 days respectively before AI vaccination. Levamisole hydrochloride 1mg/50g given at a dose of body weight, orraly through drinking water. Blood sample to measure levels of antibodies that was repeated 3 times ie on day 21, 59, and 80 days. The results showed imunododulator levamisole hydrochloride giving 3 (three) or 7 (seven) days respectively pre Avian Influenza virus vaccination of laying hens did not increase antibody level (humoral immune response). (JIIPB 2010 Vol 20 No 1: 86-91). Key words : levamisole,antibody,Avian Influenza